Outward FDI Strategies from Indonesian Multinational Enterprises - Maulana, Muhammad Fadhel; Sunitiyoso, Yos (Syntax Corporation, 2024)
This study explores the Foreign Direct Investment (FDI) strategies of three leading Indonesian multinational enterprises (MNEs)—Indofood, Adaro, and Kalbe—from the food and beverage, mining, and pharmaceutical industries. Using a thematic analysis, the research identifies three key themes shaping their internationalization strategies: Strategic Global Expansion, Operational Integration and Synergy, and Institutional and External Market Dynamics. The findings highlight how these firms leverage global expansion to diversify markets and enhance competitiveness, employ operational integration to achieve synergies and control, and adapt to institutional and regulatory challenges to mitigate risks and maintain resilience. Classical theories such as the OLI Paradigm, Internalization Theory, and Resource-Based View (RBV) provide a foundation for understanding these strategies, while contemporary frameworks like the Linkage-Leverage-Learning (LLL) Framework and Springboard Theory offer nuanced insights into the unique dynamics of emerging market multinationals (EMNEs). This study underscores the critical role of institutional alignment, regulatory compliance, and market adaptability in ensuring successful FDI outcomes. It contributes to the literature by advancing theoretical frameworks to better capture the complexities of FDI from emerging economies and offers practical recommendations for policymakers and practitioners aiming to enhance the global competitiveness of EMNEs.